Evaluación de los predictores de los estilos de vida de los estudiantes universitarios de la Amazonía peruana: un estudio transversal - Estrada-Araoz, Edwin Gustavo; Cruz-Laricano, Elizabeth Orfelia; Quispe-Aquise, Jhemy; Chura-Quispe, Gilber; Paredes-Valverde, Yolanda; Quispe-Herrera, Rosel; Gallegos-Ramos, Néstor Antonio (Retos, 2025)
Introduction: Currently, lifestyles play a key role in physical and mental health, as they influence people’s quality of life, well-being, and performance. In the university setting, factors such as depression, anxiety, and stress may negatively affect lifestyle habits, disrupting their balance and overall well-being.Objective: To determine whether depression, anxiety, and stress predict the lifestyles of university students in the Peruvian Amazon.Methodology: A quantitative, non-experimental, predictive, and cross-sectional study was con-ducted. The sample consist-ed of 652 students selected through probabilistic sampling, who were administered the Depression, Anxiety, and Stress Scale (DASS-21) and the Lifestyle Profile (PEPS-I), both with adequate psychometric proper-ties.Results: It was found that only depression has a significant predictive effect on lifestyles (β = -0.420, p < 0.01), indicating that higher levels of depression are associated with poorer lifestyles. Additionally, the model adequately fit the data (F = 78.218, p < 0.01), explaining 26.2% of the variability in lifestyles (R² = 0.262).Discussion: While some studies support these findings, further research is needed to confirm these results and analyze how depression, anxiety, and stress interact with other factors influencing life-styles.